The Language of Mathematics versus English Grammar Rules: the case of questions in Mathematics examination question papers at the University of Limpopo - Tebogo Kekana, MJ Mogoboya (Mathematical Statistician and Engineering Applications, 2022)
"The language of mathematics" has not only been a concern of the mathematics education community alone but also for linguists alike. Several substantial efforts having been made to describe its characteristics and, in particular, the ways in which it may support or cause difficulties for learners to learn mathematics. However the argument in this study is that the ‘language of mathematics’ can cause a huge obstacle if not given careful consideration. This study investigated how the type of language used in mathematics disciplines have a potential to stifle language learning. The importance of language in education cannot be over emphasized. In order to fill this gap and expand previous work on this subject matter, this study explored and identified the English grammar rules that are flouted when questions are asked in the mathematics examination question papers. We make a case that this practice impact negatively on the English writing competency of students which is very crucial for their academic performance. This article reports on the findings from the data collected in this investigation. The data for this study were collected from various selected examination papers in Mathematics and Applied Mathematics department at the University of Limpopo. Twenty (20) questions were selected from various examination question papers from 2019 to 2021 and analysed for English grammar conformity. Prescriptive Grammar theory undergird this study. The objective of this study is to present analysis of data to illustrate how English grammar rules are flouted in mathematics question papers. Analysis of the data reveals that a significant number of English grammar rules are flouted when questions are developed. The study found that found that examiners exhibit comma splice challenge (i.e. punctuation issue), lack of knowledge in question structure in English (i.e. word order). The problem of concord is also found. Furthermore, it is also found that the supposedly questions are predominately instruction and request statements that are riddled with grammatical errors. This findings reported in this article have implications for English writing pedagogy. It is hoped that these findings will help even in a small to lecturers in phrasing question in mathematics.